2020
DOI: 10.3389/fncel.2020.00170
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Ameliorates Synaptic Defects in a Mouse Model of AD by Inhibiting Cdk5 Activity

Abstract: Cyclin-dependent kinase 5 (Cdk5) is a serine/threonine kinase that is activated by the neuron-specific activators p35/p39 and plays important roles in neuronal development, synaptic plasticity, and cognitive behavior. However, the proteolytic cleavage of p35 to p25 leads to prolonged and aberrant Cdk5 activation and results in synaptic depression, highly mimicking the early pathology of Alzheimer’s disease (AD). Therefore, Cdk5 inhibition is a potential promising strategy for AD drug development. Here in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…The hippocampus is also one of the major brain regions affected by AD, in which hippocampal synaptic transmission is impaired [ 32 ]. Met has been demonstrated to ameliorate synaptic, memory and cognitive deficits in rodent models of AD [ 12 , 33 , 34 , 35 ]. However, there are few reports about Met effects on synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus is also one of the major brain regions affected by AD, in which hippocampal synaptic transmission is impaired [ 32 ]. Met has been demonstrated to ameliorate synaptic, memory and cognitive deficits in rodent models of AD [ 12 , 33 , 34 , 35 ]. However, there are few reports about Met effects on synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, improvements in language and cognitive behaviors were observed in a small sample size of Met-treated FXS patients [ 8 , 9 , 10 ]. In some Alzheimer’s disease (AD) mice models, Met attenuated amyloid plaque deposition and improved learning and memory [ 11 , 12 , 13 , 14 ]. Met also showed neuroprotective effects on dopaminergic neurons in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-modeled mice of Parkinson’s disease (PD) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the effect of metformin, a known activator of AMPK and a drug used for the treatment of type 2 diabetes, has been investigated on cognition deficits, some studies have shown an aggravating effect (Imfeld et al, 2012;Wennberg et al, 2018), whereas others reported a preventive one (Ng et al, 2014;Shi et al, 2019). Metformin has been shown to have a positive effect on AD mouse model (Wang et al, 2020). Recently it has been investigated the possible role of the AMPK isozymes in these conflicting results using mouse models of AD (Zimmermann et al, 2020).…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%
“…Metformin attenuated spatial memory deficits, neuron loss in the hippocampus, decreased Aβ plaque load and chronic inflammation in the hippocampus and cortex, and enhanced neurogenesis in the APP/PS1 mice, mouse model of AD( Ou et al, 2018 ; Chen et al, 2021 ). Metformin also restored spine density, surface AMPA subunit GluA1 trafficking, LTP expression and spatial memory in the APP/PS1 mouse by inhibiting cyclin-dependent kinase 5 hyper-activation and cyclin-dependent kinase 5-dependent tau hyperactivation( Wang et al, 2020 ). Furthermore, metformin could activate AMPK and insulin-degrading enzyme in the brain of APP/PS 1 mice, which might be the key neuroprotection mechanism of metformin( Lu et al, 2020 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatment Targeting Cognitive Function In Ad And Schizophreniamentioning
confidence: 99%